Hybrid Model of Phishing Email Detection: A Combination of Technical and Non-Technical Anti-Phishing Approaches - Al-Daeef, MM; Nurlida Basir; Madihah Mohd Saudi (Int Assoc Engineers-Iaeng, 2024)
Indexed by SCOPUS